Filósofos en 90 minutos. (Pack 1), (Derrida, Sartre, Foucault, Wittgenstein, Kierkegaard y Russell) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Pack Filósofos 1 collection brings together 6 of the most outstanding philosophers of the 19th and 20th century.
Derrida en 90 minutos -- Sartre en 90 minutos -- Focault en 90 minutos -- Wittgenstein en 90 minutos -- Kierkegaard en 90 minutos -- Russell en 90 minutos
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Foucault, Michel, -- 1926-1984.; Russell, Bertrand, -- 1872-1970.; Wittgenstein, Ludwig, -- 1889-1951.; Sartre, Jean-Paul, -- 1905-1980.; Kierkegaard, Søren, -- 1813-1855.; Derrida, Jacques; Philosophers -- Biography; Biographies; Electronic books